Phosphate reduction from waste fish farms with herbal nano gels (nano bagasse, functional nanofiber and lignocellulose nanofiber) prepared with bagasse - Fatemeh Darabitabar; Vahid Yavari; Aliakbar Hedayati; Mohammad Zakeri; Hossein yousefi (بوم‌شناسی آبزیان, 2021)
Principles of green chemistry in the production of products to reduce and eliminate environmental pollutants can introduce products such as nano-gels as environmentally friendly and biodegradable adsorbents. Freshwater supply is one of the most important goals in improving the infrastructure of aquaculture and industry due to repeated droughts. For this reason, wastewater treatment and reuse can be a suitable way to meet the country's water needs. The purpose of this research was to use herbal nano-gels from agricultural waste (bagasse) to remove phosphate from wastewater treatment. First, the bagasse nano gels were prepared by a mechanical and a top-down mechanism. Optimal values were calculated for each parameter. The optimum amount of dosage, pH, concentration, time was determined 0.2 g, 0.3 g for nano-gel, 5, 100 mg/l, 30 minutes. According to the equations, the adsorption isotherm was the most consistent with the Langmuir model and Temkin and Pseudo-second-order. The results showed that bagasse nano-hydrogels can remove phosphate by less than 0.5 mg/l.